Racionalidades pedagógicas na música em cursos de pedagogia: um estudo no Rio Grande do Sul - Dallabrida, Iara Cadore (2019)
This thesis report was carried out under the Graduate Program in Education of the Federal University of Santa Maria, in the research line Education and Arts and is linked to the research group FAPEM: Training, Action and Research in Music Education. His general objective was to understand pedagogical rationalities of Music in courses of Pedagogy of Rio Grande do Sul from narratives of teachers who work in Arts and / or Music disciplines in these courses. Specifically, it sought to know the formation and life trajectories of these subjects, to identify what knowledge / contents / experiences and methodologies are developed, why they choose them and to apprehend meanings that the formators attribute to Music. The theoretical framework that underlies the research was constructed from the studies on Teacher Thought (CLARK, PETERSON, 1984, PACHECO, 1995, GARCIA, 1995, PEREZ-GOMES, 1998 and, in Musical Education, BEINEKE, 2000; DEL BEM, 2001; LOURO, 2004, SOUZA, 2010), when considering the teacher a reflective professional (SCHÖN, 2000, DEWEY, 1910; Zeichner, 2008) is a mobilizer of knowledge (GAUTHIER, 1998; TARDIF; LESSARD; LAHAYE , 1989), motivated the concept of pedagogical rationality (CARVALHO, 2007), understood as the pedagogical reasons of the teacher. In order to understand such rationalities, which are constituted in the significances and meanings (VYGOTSKY, 2009) constructed by the subjects, the Analysis by Nuclei of Significances (AGUIAR; OZELLA, 2003; 2006). It was concluded that the pedagogical rationalities in Music in Pedagogy courses have developed: a) Music as sounds; b) Music as language; c) Music while school activities; d) Music as a creative expression. However, these rationalities are singular and hybrid (Canclini, 2012) because the formators corroborate and diverge, at the same time, about ways of being of Music in the formation of the teacher of reference, from frames of reference (DEL BEN, 2001; CARVALHO, 2007) built on the personal-academicprofessional experiences of these formators.